A novel splice site mutation of the ATM gene associated with ataxia telangiectasia - Saeidi, Kolsoum; Saleh-gohari, Nasrollah; Mansouri Nejad, Seyed Ebrahim (Iranian Journal of Child Neurology, 2018)
Abstract Objective: Ataxia telangiectasia (AT) is a rare autosomal recessive disorder caused by mutation in the Ataxia telangiectasia mutated (ATM) gene. This disorder is characterized by progressive cerebellar ataxia, telangiectasia, immunodeficiency and a predisposition to leukemia/lymphoma. Methods: In this study, four members of a family including a symptomatic AT patient, his parents and sibling were examined for ATM gene defects. DNA was extracted from peripheral leukocytes and the coding regions and exon-intron boundaries of ATM gene were amplified by next generation sequencing technique. The identified mutation was tested in all members of the family. Results: Molecular analyses identified a homozygous T to G substitution in c.7308-6 position resulting in a novel acceptor splice site in intron 49 of the ATM gene in the index patient. Parents and sibling of the proband were heterozygous for the same mutation. Conclusions: The variant c.7308-6T>G is predicted to be pathogenic due to impaired splice site causing exon skipping. This newly found frameshift mutation cosegregated as an autosomal recessive trait as expected for Ataxia telangiectasia syndrome.